There are no provinces in the Internet - Bulgakova, Elena (project baikal, 2020)
The article is devoted to the problem of the development of online forms of architectural education. The processes of the development of architectural education from Vitruvius to the present day are examined. Two different paradigms of such learning are highlighted. The combinatorial paradigm is based on a finite set of standard elements and considers design as a combination of these elements according to predetermined rules. The second paradigm (metamorphic) interprets architectural design as a continuous process of creative development of the original idea. Education in this case is based on the constant interaction of the teacher and student and their joint creative search. It is concluded that it is necessary to synthesize two paradigms in order to create a complete online education in the architectural field.
Keywords: online education; architecture; architectural education; history; paradigm